Budget Plan Information System Distributed Network In PT. Cipta Aparta - Darwas, Rahmadini; Vitriani, Rizka (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2016)
Information Systems Budget Plan (RAB) is created using information from a number of data ie data processing tender documents or data relating to the auction that will be followed. Budget Plan Information system can be applied in the problem of preparing the Budget Plan, that facilitate in making the tender documents. All the required data will be grouped and stored in a database so asÂ to minimize errors in the calculation process of making budget plan fee. Currently manufacture Budget plan is not going well, part of the operator PT. Cipta Aparta have difficulty in classifying the data and the frequent occurrence of errors during the process of arithmetic. therefore the use of information technology and communications bring the idea to create a Information System Budget Plan (RAB) Development of Distributed Networks (Medium, Low, and Substation) atÂ PT. Cipta Aparta with C # and MySQL.